Niger : Eighth Review Under the Extended Credit Facility Arrangement and Request for Waivers of Nonobservance of Performance Criteria and for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the ED. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses Niger's Eighth Review Under the Extended Credit Facility (ECF) Arrangement and Request for Waivers of Nonobservance of Performance Criteria (PC) and for Modification of PCs. Niger's medium-term prospects are closely linked to returns on major projects in oil and mineral extraction that are under way. Two of the end-2015 PC for the eighth ECF review were missed (on domestic financing and domestic arrears repayment), as were several indicative targets. The IMF staff supports the authorities' request for waivers for the unmet PC on domestic financing and domestic arrears repayments at end-December 2015.